The genetics and epigenetics of satellite centromeres - Talbert, Paul B.; Henikoff, Steven

(untitled) (Genome Research, 2022)
Centromeres, the chromosomal loci where spindle fibers attach during cell division to segregate chromosomes, are typically found within satellite arrays in plants and animals. Satellite arrays have been difficult to analyze because they comprise megabases of tandem head-to-tail highly repeated DNA sequences. Much evidence suggests that centromeres are epigenetically defined by the location of nucleosomes containing the centromere-specific histone H3 variant cenH3, independently of the DNA sequences where they are located; however, the reason that cenH3 nucleosomes are generally found on rapidly evolving satellite arrays has remained unclear. Recently, long-read sequencing technology has clarified the structures of satellite arrays and sparked rethinking of how they evolve, and new experiments and analyses have helped bring both understanding and further speculation about the role these highly repeated sequences play in centromere identification.